Gender and Age Differences in Sleep Problems in Children: Person-Oriented Approach With Multigroup Analysis. Issue 3 (4th May 2019) - Chen, Yi-Lung; Tseng, Wan-Ling; Yang, Li-Kuang; Gau, Susan Shur-Fen
ABSTRACT: Objective/Background : This study aimed to identify subtypes of sleep problems in children and to examine whether these patterns differed between gender and age groups. Participants : There were 3, 052 children (951 elementary school boys, 943 elementary school girls, 603 junior high school boys, and 555 junior high school girls) aged 7–16 years from two school-based epidemiological samples. Methods : Sleep problems were measured by the Sleep Habit Questionnaire based on parent reports. Results : Using the latent class modeling, a person-oriented approach, with a multigroup analysis, we identified four classes of sleep problems: moderate to high sleep problems (1.1%–3.1%), sleep-related breathing problems and parasomnias dominant (14.9%–21.1%), insomnias dominant and parasomnias (1.0%–3.1%), and no or low sleep problems (74.7%–81.4%), with varied prevalence rates of sleep problems across gender and age groups. Conclusions : This study identified four classes of sleep problems across gender and age groups but with different prevalence rates of sleep problems, suggesting the complex interaction of gender and age in the subtypes of sleep problems. The gender- and age-specific interventions for sleep problems are suggested. Future studies are warranted to replicate these classes and to identify associated factors with each class.